Trabalho cooperativo no MST e ensino fundamental rural: desafios à educação básica - Marlene Ribeiro (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
The purpose of this paper is toidentify those challenges which cooperative work, developed by settled farmers, raise for theprimary school. The methodology involves a literature review about economic solidarity and action-research carried out in settlements established by the Land Reform and in rural schools in the municipality of Piratini/RS. The research focuses on the relation between cooperative work and school education. The discourse of the subjects of the research reveals the conflict between the formation required for cooperative agricultural work and the model of basic education on which rural education is based.